Neonatal ovarian cyst complicating as subacute intestinal obstruction: a case report - Chakraborty, Goutam; Chakraborty, Anwesa; Sugandhi, Nidhi; Jadhav, Amit; Acharya, S. K.; Bagga, Deepak (International Journal of Contemporary Pediatrics, 2020)
Congenital Ovarian cysts are among the commonest intra-abdominal masses encountered in foetuses on antenatal screening, mostly during the third trimester of pregnancy. Though the etiology remains unknown, the most prevalent hypothesis holds maternal hormonal stimulation responsible for the pathology. Most are asymptomatic but potential complications can be life-threatening. A case of a 7 day old female baby was reported with normal antenatal scans and complaints of abdominal distension and vomiting since day 1 of life. Imaging included a Ultrasonographic diagnosis of suspected ovarian lesion and an MRI diagnosis of omental cyst. Due to progressive abdominal distension, authors proceeded with laparotomy. Left salpingo-oophorectomy was done as no ovarian tissue was salvageable. Post-operative period was uneventful. The histopathological picture was that of benign follicular cyst of ovary.